The Effect of Nutrition Education Given to Healthcare Personnel on Orthorexia Nervosa - Dalğa, Derya; Öngün Yılmaz, Hande (Progress in Nutrition, 2021)
Objective: This study was conducted to determine the effect of nutritional education given to healthcare professionals on Orthorexia Nervosa. Methods: Within the scope of the study, 111 volunteer health personnel working in a private health institution received nutrition education. Before the education, the questionnaire form and ORTO-15 scale were applied to the participants by face-to-face interview technique, and their anthropometric measurements were taken by the researcher. ORTO-15 scale was applied again after the education. Results: Of the individuals who participated in the study, 75.7% were female, 24.3% were male and the mean age was 32.75±10.37 years. The mean BMI of the participants was 24.94±4.03 kg/m2, and the mean BMI of males was significantly higher compared to females (p<0.05). While the mean ORTO-15 score before the education was 37.35±3.62, it increased to 42.51±4.01 after the education (p<0.001). According to the pre-education ORTO-15 scores of the participants, 11.7% of them had orthorexia, and this rate was only 0.9% after the education. Conclusion: At the end of the study, it was determined that providing nutrition education to healthcare personnel had a positive effect on them in terms of overcoming orthorexia. Nutritionists should give nutrition education with wide participation that includes different groups to decrease the tendency towards orthorexic behaviors in society.